2016
DOI: 10.1017/s0958344016000094
|View full text |Cite
|
Sign up to set email alerts
|

Digital stories: Bringing multimodal texts to the Spanish writing classroom

Abstract: Despite the availability and growing use of digital story software for authoring and instructional purposes, little is known about learners’ perceptions on its integration in the foreign language writing class. Following both a social semiotics approach and activity theory, this study focuses on six advanced Spanish learners’ perceptions about the production of a digital story in which they integrated a variety of modes (written, oral, images, sounds) and manipulated the semiotic resources within each mode (si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 28 publications
1
31
0
7
Order By: Relevance
“…As a result of the study, it is seen that the digital storytelling contributes to the development of reading, speaking, listening, visual reading and presentation skills. These results overlap with the results which show that the digital storytelling contributes to various language skills in the language education (Mathison & Pohan, 2007;Norman, 2011;Oskoz & Elola, 2016;Sylvester & Greenidge, 2010).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As a result of the study, it is seen that the digital storytelling contributes to the development of reading, speaking, listening, visual reading and presentation skills. These results overlap with the results which show that the digital storytelling contributes to various language skills in the language education (Mathison & Pohan, 2007;Norman, 2011;Oskoz & Elola, 2016;Sylvester & Greenidge, 2010).…”
Section: Discussionsupporting
confidence: 55%
“…Araştırma sonucunda ayrıca dijital öykülemenin okuma, konuşma, dinleme, görsel okuma ve sunu becerilerinin gelişimine de katkı sağladığı görülmüştür. Yaratıcı bir dil öğrenme aracı olan dijital öykülemenin, dil eğitiminin amaçlandığı derslerde çeşitli dil becerilerinin gelişimine katkı sağladığına ilişkin sonuçlarla örtüşmektedir (Mathison & Pohan, 2007;Norman, 2011;Oskoz & Elola, 2016;Sylvester & Greenidge, 2010). Değişen metin algısının yanı sıra dijital argümanların, öğrenme-öğretme sürecine uyumu sağlamasıyla (Kulla-Abbott & Polman, 2008) temel dil becerileri ve teknolojik becerilerin eş güdümlü kullanımına olanak sağladığı söylenebilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Digital storytelling has been increasingly integrated into language classrooms (Oskoz & Elola, 2016). Digital storytelling is an educational practice that has received attention in the literature, such as studies by Robin (2006), who stated that "Digital Storytelling has become a powerful instructional tool for both students and educators" (Robin, 2006: 709).…”
Section: Solutions With Digital Storytelling For Foreign Language Educationmentioning
confidence: 99%
“…Because research has shown that students' performance is influenced by their understanding and expertise with digital tools (DTs) (Oskoz and Elola 2016;Zapata 2018), and in order to avoid any type of exclusion, students were given the freedom to choose and use any (digital) tool they wanted to create their art-either because they were familiar with it or because they wanted to experiment with it. The most used DT was Adobe Photoshop.…”
Section: When Writing Meets (Digital) Artmakingmentioning
confidence: 99%